Distribution of catheterisation laboratories in Indonesia 2017-2022: a nationwide surveyResearch in context - Farizal Rizky Muharram; Chaq El Chaq Zamzam Multazam; Wigaviola Socha Harmadha; Andrianto Andrianto; Senitza Anisa Salsabilla; Iwan Dakota; Hananto Andriantoro; Doni Firman; Maya Marinda Montain; Radityo Prakoso; Dilla Anggraeni (Elsevier, 2024)
Summary: Background: Geographical terrains of Indonesia pose a major hindrance to transportation. The difficulty of transportation affects the provision of acute time-dependent therapy such as percutaneous coronary intervention (PCI). Also, Indonesia's aging population would have a significant impact on the prevalence of acute coronary syndrome in the next decade. Therefore, the analysis and enhancement of cardiovascular care are crucial. The catheterisation laboratory performs PCI procedures. In the current study, we mapped the number and distribution of catheterisation laboratories in Indonesia. Methods: A direct survey was used to collect data related to catheterisation laboratory locations in July 2022. The population data was sourced from the Ministry of Home Affairs. The recent growth of catheterisation laboratories was examined and evaluated based on geographical areas. The main instruments for comparing regions and changes throughout time are the ratio of catheterisation laboratories per 100,000 population and the Gini index (a measure of economic and healthcare inequality. Gini index ranges from 0 to 1, with greater values indicating more significant levels of inequality). Regression analysis was carried out to see how the number of catheterisation laboratories was affected by health demand (prevalence) and economic capacity (Gross Domestic Regional Product [GDRP] per Capita). Findings: The number of catheterisation laboratories in Indonesia significantly increased from 181 to 310 during 2017-2022, with 44 of the 119 new labs built in an area that did not have one. Java has the most catheterisation laboratories (208, 67%). The catheterisation laboratory ratio in the provinces of Indonesia ranges from 0.0 in West Papua and Maluku to 4.46 in Jakarta; the median is 1.09 (IQR 0.71-1.18). The distribution remains a problem, as shown by the high catheterisation laboratory Gini index (0.48). Regression shows that distribution of catheterisation laboratories was significantly affected by GDRP and the prevalence of heart disease. Interpretation: The number of catheterisation laboratories in Indonesia has increased significantly recently, however, maldistribution remains a concern. To improve Indonesia's cardiovascular emergency services, future development of catheterisation laboratories must be better planned considering the facility's accessibility and density. Funding: Airlangga Research Fund - Universitas Airlangga.